What snippet size is needed in mobile web search? - Kim, Jaewon; Thomas, Paul; Sankaranarayana, Ramesh; Gedeon, Tom (Proceedings of the Conference on Computer-Human Information Interaction and Retrieval, 2017)
A snippet (content summary for a web page) is one of the main elements in a search result page. Search engines have been improved to reduce users' effort in web search, e.g., providing flexible snippet sizes by considering the purpose of the search and suggesting predicted answers. In most cases, search engines for mobile devices present two or three lines of snippet for each result link. Some studies suggest that long snippets provide a better search experience on desktop screens, but this may not be true for mobile devices because of the smaller screen. We conducted a user study to investigate what size of snippet is appropriate for mobile devices. Our findings suggest that users with long snippets on mobile devices exhibit longer search times with no better search accuracy for informational tasks. This is caused by the longer reading time, frequent scrolling with bigger viewport movements, and greater time consumption for searching and reading one result. The overall findings suggest that, unlike desktop users, mobile users are best served by snippets of two to three lines.